Structural insights into measles virus RNA synthesis regulation and pan-paramyxoviral polymerase inhibition by ERDRP-0519 - Tianjiao Du; Jiening Wang; Chengji Yang; Rubing Xue; Ying Chen; Kaiyue Jie; Xiaokang Zhang; Long Zhang; Gaojie Song; Qiansen Zhang; Shan Wu; Heng Ru (Proceedings of the National Academy of Sciences, 2026)
Nonsegmented negative-sense RNA viruses (nsNSVs) rely on a multifunctional RNA-dependent RNA polymerase (RdRP) complex for transcription and replication. In measles virus (MeV), the nonstructural protein C has long been implicated in regulating RNA synthesis, yet its precise role remains unclear. Here, we show that the MeV C protein directly associates with the RdRP complex. Using cryoelectron microscopy, we determined atomic-resolution structures of the MeV polymerase with and without C, revealing that C binding stabilizes the C-terminal region of L and locks the complex into a replication-competent elongation state. Biochemical data further show that C promotes N protein recruitment, enhancing polymerase processivity through facilitating encapsidation during replication. Additionally, we also resolved high-resolution structures of MeV and Nipah virus (NiV) polymerases bound to ERDRP-0519, an orally available morbillivirus inhibitor. Unexpectedly, the compound occupies an allosteric pocket within the RdRp domain rather than the previously predicted PRNTase domain, overlapping conserved resistance sites. This binding induces conformational changes in palm subdomain, blocking RNA template and nucleotide engagement, thereby halting RNA synthesis. These findings uncover distinct regulatory and inhibitory mechanisms in paramyxovirus polymerases and provide a structural framework for the rational design of broad-spectrum antivirals targeting MeV, NiV, and potentially other clinically relevant nsNSVs.